ICU admission and outcomes in a community-based tertiary care hospital: an audit of one year (Health Renaissance, 2011)
Background: The most serious patients requiring advanced organ system support are admitted in the Intensive Care Unit (ICU) of hospitals for achieving better outcome. B.P.Koirala Institute of Health Sciences (BPKIHS) hospital ICU is the only multidisciplinary unit that has been catering care for the whole of the eastern region of Nepal. Medical audit of ICU provides important feedback for improvement in care and policy making. Objectives: To audit the indications analyse and outcome of patients admitted to the multidisciplinary ICU of BPKIHS in a period of one year. Methods: Data of all the ICU admitted patients for the period of one year were analyzed retrospectively from the ICU register and patients’ folder. The variables analysed included age, gender, diagnosis, duration of ICU stay and outcome. Results: Altogether 255 patients were admitted in the study period; 150 (58.8%) males and 105 (41.2%) females. Majority (49%) were surgical patients followed by medical (39%). Mean duration of stay was 8 days. Discharge rate was 61% and the mortality rate was 26%. Thirteen percent of the patients left against medical advice (LAMA). Admission from operation theatre and emergency ward was associated with better outcome while admission from general wards was associated with poor outcome. Peritonitis with sepsis was associated with the worst outcome; organophosphorous poisoning was associated with good outcome. Conclusion: The most common patients admitted in the multidisciplinary ICU of BPKIHS are mostly general surgical and general medical. Significant fractions of the patients admitted in the ICU are taken home by their relatives against medical advice. Keywords: intensive care unit; organ support; audit; BPKIHS. DOI: http://dx.doi.org/10.3126/hren.v9i2.4978 Health Renaissance 2011: Vol.9 (No.2): 83-87